Public relations practitioners’ perception of new media influence on promotion of mutual understanding between organisation and strategic publics in Nigeria - Igben, Harvey G.O.; Ilaya, Michael E. (Linguistics and Culture Review, 2021)
New media is a trending innovation and its influence in the promotion of mutual understanding between organizations and strategic publics is a more contemporary issue. This study evaluates the perception of public relations practitioners on the incorporation of new media into the process of promoting good relationships between organizations and strategic publics in Nigeria. The fundamental goal is to examine if public relations practitioners find new media helpful in carrying out public relations activities in their organizations. This study is hinged on Technological determinism theory. Findings show that public relations practitioners of both public and private organizations do perceive the adoption of new media technologies in the performance of their function for the promotion of mutual understanding as supportive to quick and interactive approaches to dissemination of information from organizations to strategic stakeholders and the public. The study recommends that more public relations practitioners of organizations especially public organizations should be encouraged to use new media in course of executing their professional assignments.